2010
DOI: 10.2174/1876388x01002010192
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advances in Current PET and Hybrid Imaging Systems

Abstract: Abstract:The continuing efforts of investigators to achieve the best physical and clinical performances from PET (positron emission tomography) and related hybrid cameras (PET/CT and PET/MRI) have led to remarkable technical advances in hardware and software.Time of flight (TOF) information measurement, which has been enabled thanks to the invention of fast, heavy crystals and advances in fast light detection sensors and readout electronics, is used to obtain the PET images of better quality and lesion-detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 84 publications
(115 reference statements)
0
21
0
Order By: Relevance
“…In a previous study, we showed a 1-ns coincidence timing resolution using LYSO/SiPM detector pairs (11). Moreover, there is increasing evidence that SiPM is feasible for time-of-flight measurement (8,28). A coincidence timing resolution of 240 ps can be achieved with LYSO and multipixel photon counter (MPPC, the SiPM provided by Hamamatsu Photonics) couplings under optimal conditions of bias voltage and temperature (12).…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study, we showed a 1-ns coincidence timing resolution using LYSO/SiPM detector pairs (11). Moreover, there is increasing evidence that SiPM is feasible for time-of-flight measurement (8,28). A coincidence timing resolution of 240 ps can be achieved with LYSO and multipixel photon counter (MPPC, the SiPM provided by Hamamatsu Photonics) couplings under optimal conditions of bias voltage and temperature (12).…”
Section: Discussionmentioning
confidence: 94%
“…The radial distribution of the detectors can be varied. For human whole body and brain imaging PET diameters are approximately 70-87 cm and 40-50 cm, respectively (Lee , J.S., 2010;Moses, W.W. et al, 1997). The further the detectors are placed apart the more likely the gamma signal will deviate from 180 o C (i.e.…”
Section: Human Pet Camerasmentioning
confidence: 99%
“…For this purpose, PET imaging techniques [4,5,6,7] for measuring concentrations of positron-emitting radioisotope within the tissue of living subjects have been developed by researchers from diverse disciplines for the last decade. Since the first introduction of PET to medical imaging applications in the late 1960's, it has already grown into a well-researched, highly evolved field [8,9,10].…”
Section: Introductionmentioning
confidence: 99%